The effect of venture capital investment on banks performance in systematic approach - ALi Foroush Bastani; Hamed Hamedinia; mohammad Ghajari (پژوهش‌های برنامه و توسعه)
Venture Capitals (VCs) which have recently financed significant amounts of start-up companies, are divided in two categories: Independent Venture Capital (IVC) and Bank-affiliated Venture Capital (BVC). In order to study the effect of VC on bank performance, it is necessary to analyze the various financial and economic variables and their relation. Since the relation between these variables is extremely enormous and complex, it is not possible to use econometrics and classical financial models. Therefore, a system dynamic approach is used in this paper to analyze the problem. The problem is studied in two stages; first, the consequences of bank’s invest in VC industry is investigated and second, a comparison is made between the BVC and IVC. The results show that bank with investing in VC is benefited from both yield of VC projects and also presenting more loans. Finally, using the designed systematic model, the proper proportion, with which bank should invest in VC to optimize its profits, is calculated.